Papa, Elena - (:unkn) unknown (My University, 2026)
CURRICULUM VITAE Personal Details: Surname: PAPA Name: ELENA Title: Instructor Language Centre Cyprus University of Technology Cyprus Born: July 28th 1970, Famagusta – Cyprus Nationality: Cypriot Marital Status: Divorced, two children Contact details: Home address: Kratinou 5A, Ayios Ioannis, 3012 Limassol Office Telephone: + 357 25002025 Home Telephone: + 357 25101242 Mobile Telephone: +357 99414181 E-mail: elena.papa@cut.ac.cy Education: Dates: 10/2020 – today Title of qualification will be awarded in Jan 2022: MSc in Digital Merketing , Neapolis University Principal subjects: • Digital Marketing • Research Methods and Data Analysis • Marketing Management & Business Communication • e- Consumer Behavior • Digital Communication and Social Media Strategies • Big Data and Marketing Analytics • Entrepreneurship and Innovation • Disruptive Technologies Date: 24/11/2020 Title of qualification awarded : Digital Marketing and Sales Diploma ,Adonis Business Academy Dates: 02/2009 – 01/2015 Title of qualification awarded : Master of Business Administartion , University of Leicester Information Technology Management Principal subjects: • Foundations of Knowledge and Professional Skills • Organizational Behaviour • Accounting for Managers • Marketing Design & Operations • Strategy, Business Information & Analysis • Corporate Finance • Business Ethics in a Global Context • Management Information System Development • Project Management of Information Technology • Dissertation – Management of Information Systems : The effectiveness of e-learning as a teaching method for open and distance learning in academic and professional institutions in Cyprus Dates: 1987 – 1990 Title of qualification awarded : Diploma of the Higher Technical Institute Principal subjects: Computer Programming, Mathematics I, Data Processing, Business Organiation & Accounts, English & Communication I, Systems Analysis and Desing I, Operating Systems, Data Communication, Quantitative Methods II, Report & Business Writing, Data Structures, Commercial Data Base Package, Systems Analysis and Desing II, Advanced Operating System Consepts & Design , On Line Systems , Computer Graphics, System Design & Implementation, Software Engineering, Data Base Management Systems, Web Design, Artificial Intelligence , Expert Systems Name and type of oranisation providing education and training : Higher Technical Institute, Nicosia Weighted Average : 73.4 / 100 Dates: 1981 – 1987 Title of qualification awarded : Higher Education Degree Principal subjects / Occupational skills covered : Mathematics, Physics, Chemistry, English Language, Modern Greek Name and type of oranisation providing education and training : Ayios Antonis Lyceum of Limassol Weighted Average : 19 1/11 Languages: - Greek (excellent) - English (very good) Professional Experience: 1990 – 1992 Seasonal Lab Assistant in Computer Studies Department (Higher Technical Institute-HTI) 1/9/1992 – 31/12/2007 Lab Assistant in Computer Studies Department Higher Technical Institute-HTI) Duties: I was responsible of helping the students as also the lecturers during the various lessons, preparing the inventory of the laboratories, installing various software packages in the computers, fixing the computers when they were broken. Additionally of my duties I was responsible of my department´s student grading system meaning entering the student’s grades and issuing their performances. 1/1/2008 – 31/12/2014 Computer Instructor Department of Nursing Cyprus University of Technology Duties: I was responsible of helping the students as also the lecturers during the various lessons, preparing the inventory of the laboratories, installing various software packages in the computers, fixing the computers when they were broken. 1/1/2015 – today Senior Instructor Language Centre Duties: I am responsible and accountable for the smooth running of Language Centre computer systems, organize and maintain the various technology infrastructures used in the department. I make sure that business equipment is updated to work effectively and give maximum results, troubleshoot computers and operating systems that are malfunctioning to identify faults and fix them by self or get an expert engineer to fix more difficult issues. I attend workshops/conferences to learn latest Information Technology Management techniques, additionally I organize workshops for Language Centre staff to intimate them with the latest trends in education. Furthermore I develop the marketing strategy, co-ordinate, plan and implement marketing campaigns for the promoting the MA in CALL, the online Master offered by the Language Centre & Department of Multimedia and Graphic Arts. Besides I operate and maintain the Language Centre websites and social media accounts, evaluate the results so that to monitor and report on effectiveness of marketing communications strategies and come up with appropriate courses of action. Furthermore, the last six years I have my radio program at CUT radio called “ Γλωσσικά Ακούσματα" , that it deals with the Language Centre and the CUT studentship issues, promotion of undergraduate and postgraduate programs, interviews with CUT staff , students and other guests. Furthermore, I have taught the workshop of Introduction to Νew Μedia - CIS 103, of the undergraduate Degree in Communication and Internet Studies, offered by the Faculty of Communication and Media Studies. I am also a member of CUT choir. Endorsement Courses/ Seminars/Conferences: 1. Course on ”Netware 4.x Administration” , November 1996 , Nicosia CYPRUS 2. Course on ”Tru64 UNIX Administration” , October 1999 , Nicosia CYPRUS 3. Participation at the ‘International Conference on Digital Information and Communication Technology and its applications;, June 21-23 2011, Paris FRANCE 4. Course on ” Access for Managers” ,November 2004 , Nicosia CYPRUS 5. Seminar on ”Implementing and Supporting Microsoft Windows XP Professional – Course 2272” , 23rd March – 8th September 2005, Nicosia CYPRUS 6. Course on ” Dreamweaver 8 Introduction & Intermediate” , November 2007, London UK 7. Participation at the ‘Innovative Learning Environments 2011, Visual Thinking , Visual Learning’, 24th of September 2011, Nicosia CYPRUS 8. Participation at the ‘Networking: Language Centres and the challenge of creating networks', 12 – 13rd of May 2015, Sienna ITALY 9. Participation on the ‘23rd EuroCALL conference CALL Communities and Culture, 24 – 27th of August 2016, Limassol CYPRUS 10. Participation on the ‘International Conference of Education , Research and Innovation’ ,14 – 16th of November 2016, Seville SPAIN 11. Participation on the ‘International Conference on Global Education, Teaching and Learning, Management, Economics, Business and Marketing’, 25 - 26th of November , Vienna AUSTRIA 12. Participation at the ‘23rd TESOL Arabia International Conference and Exhibition’, March 9-11 2017, Dubai 13. Universidade Federal Fluminense, Niteroi, Rio DeJaneiro,Brazil, Erasmus program, 22-26 May, 2017 14. Participation at the ‘20th International Conference on Teaching, Education & Learning(ICTEL)’ , 26 – 27 of July 2017, Barcelona SPAIN 15. Participation at the Conference on ‘Adult Education Policy and Practice: Gamification ,Entrepreneurship Education, and Education Policies’ Online Game for Entrepreneurship and Innovation(EntrInno) , 12th of October 2017, Nicosia CYPRUS 16. Course on “Certified Social Media Manager”, Adonis Business Academy, 16- 18 of October 2017, Limassol CYPRUS 17. Course on “Certified Google Advertising Professional “,Adonis Business Academy, 13- 15 of November 2017, Limassol CYPRUS 18. Course on “ Human Resource Management”, Adonis Business Academy, 20- 21 of November 2017, Nicosia CYPRUS 19. Participation at the ‘8th International Conference on Languages, Social Sciences, Education and Interdisciplinary Studies (ICLSSE-17) Dec. 4-6, 2017 London (UK) 20. Participation at the ‘39th Annual International Convention be Creative and Inspire! (TESOL Greece) ’, 3-4 of March 2018, Athens GREECE 21. Participation at the ‘37th Annual International TESOL France Colloquium, Beyond the Classroom ‘,held in Paris, France at TELECOM ParisTech on 16th –18th November 2018 22. Course on “Certified in Internet Marketing & S.E.O”, Adonis Business Academy, 7 - 8 of March 2018, Limassol CYPRUS 23. Participation at the '2nd International Conference on Language Education and Culture’ held in Istanbul Medipol University TURKEY, Istanbul,27 June 2019 24. Seminar on «INTERNET MARKETING: Online Επιχειρηματικότητα», - 26 of April 2020, Limassol Cyprus 25. Course on “The manual of the great Salesman in the world ”, Adonis Business Academy, 23-24 November, 2020, Limassol CYPRUS 26. Many other short seminars/courses/workshops held in Cyprus, and other countries, and organized by professional bodies. Other Professional Activities: - Member of the Departmental Academic Board, of HTI (2005 – 2008). - Member of the Staff Union of HTI (November 2007-2008). Skills and Interests: Social skills and competences: Friendly, enjoyable, patient, communicative, sociable, general knowledge about politics, sports, music Computer skills and competences: o Very good knowledge of computer programming o Excellent knowledge of MS Office (Word, Excel, Access etc) o Ηas knowledge of a wide range of marketing techniques and concepts o Social Media Skills o Good teamwork skills o Communication skills and networking ability o Good organization and planning skills o Knowledge of media production, communication and dissemination techniques and methods o Radio broadcasting Interests and other skills: Music, gymnastic, reading literature, football Date: 10 of May, 2020
Keywords: education , distance learning, computer assisted language learning; computer